PEMELIHARAAN HUBUNGAN ANTARA ORANGTUA YANG BERCERAI DAN ANAK (STUDI KUALITATIF DESKRIPTIF KOMUNIKASI ANTARPRIBADI ANTARA ORANGTUA YANG MEMILIKI HAK ASUH DENGAN ANAKNYA) - Oksyta Wulandari (Komuniti: Jurnal Komunikasi dan Teknologi Informasi, 2016)
Family is the smallest social unit in the society. Family also has an important role in the personal development in a child. However, today divorce rate in Indonesia has increased and divorce will harm people involved, including children. Divorce triggers weakens relationship between parent and children. In relational maintenance there are several behaviors used to maintain relational maintenance between parent and children. So the researcher was interested to know relational maintenance behaviours between divorced parents who had custody of their children with their children. In this study the researcher used qualitative research method and purposive sampling as the sampling technique. The informants were: divorced man or woman who has custody of their child and the man or woman’s child. Three people were from each group were interviewed, totaling in 6 informants. The method to test data validity has source triangulation method by comparing interview and observation result from all data sources, and only selecting consistant data which has then used as data. The result of this showed that the applications of relational maintenance behaviours between parent who had custody of their children with their children consisted of several types,including positivity, openness and routine talk,assurances, task and sharing, supportiveness,joint activities, humor, and constructive conflict management. However not all relational maintenance behaviors do by divorced parents who had custody of their children with their children. Some relational maintenance behaviors performed by divorced parents who had custody of their children with their children were: positivity, supportiveness, joint activities, humor, and constructive conflict management. Meanwhile, relational maintenance behaviors that is not performed by divorced parents who had custody of their children with their childrenwere: openness and routine talk and task and sharing that based on the lack of frequency of face-to-face between parents and children. Generally, relational maintenance performed by parent who had custody of their children with their children.